2021
DOI: 10.1128/mbio.00219-21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Viral Glycoprotein Targeting by Membrane-Associated RING-CH Proteins

Abstract: An emerging class of cellular inhibitory proteins has been identified that targets viral glycoproteins. These include the membrane-associated RING-CH (MARCH) family of E3 ubiquitin ligases that, among other functions, downregulate cell surface proteins involved in adaptive immunity. The RING-CH domain of MARCH proteins is thought to function by catalyzing the ubiquitination of the cytoplasmic tails (CTs) of target proteins, leading to their degradation. MARCH proteins have recently been reported to target retr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 71 publications
7
60
1
Order By: Relevance
“…Next, we showed that MARCH8 mRNA expression in 293T cells ( Fig. 4A ) was reduced between 2 and 24 h after (i) exposure to type I interferon (IFN) or (ii) infection with IAV, whereas IFN-regulated gene IFITM3 was strongly upregulated by both type I IFN and by IAV infection; it should be noted that previous studies reported rapid (0.5 h) induction of MARCH8 by type I IFNs in 293T cells, which returned to baseline levels within 2 to 4 h ( 8 ). Similar results were seen using human monocyte-derived macrophages (hMDMs) ( Fig.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Next, we showed that MARCH8 mRNA expression in 293T cells ( Fig. 4A ) was reduced between 2 and 24 h after (i) exposure to type I interferon (IFN) or (ii) infection with IAV, whereas IFN-regulated gene IFITM3 was strongly upregulated by both type I IFN and by IAV infection; it should be noted that previous studies reported rapid (0.5 h) induction of MARCH8 by type I IFNs in 293T cells, which returned to baseline levels within 2 to 4 h ( 8 ). Similar results were seen using human monocyte-derived macrophages (hMDMs) ( Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Differences in the relative proportion or the absolute amount of specific viral proteins in a packaged virion could contribute to overall reduction in IAV infectivity. Reduced incorporation of Env into HIV-1 ( 14 ) or VSV-G, EboV-GP, and SARS-CoV-2 S glycoproteins into pseudotyped particles ( 8 ) correlated with reduced infectivity of virions released from MARCH8-expressing cells. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations